Linguistic universals and language change - Good, Jeff. (New York ; Oxford : Oxford University Press, 2008)
Leading scholars examine and assess rival explanations for linguistic universals and the effectiveness of different models of language change. They illustrate their arguments with a very wide range of reference to the world's languages.
Description based on print version record.
Keywords: Universals (Linguistics); Linguistic change; Typology (Linguistics)